Pendampingan Pemanfaatan Duolingo melalui Smartphone Sebagai Alat Pengajaran dan Pembelajaran Bahasa Inggris Bagi Masyarakat - Raden Agus Budiharto; Abdul Wahab Syahroni (Ilin Institute, 2020)
The community service activity is aimed at providing a great command of Duolingo application for English teacher and MA Miftahul Ulum Pagendingan students where the application can be utilized as an interesting English teaching and learning tool. The method employed in this activity is training and mentoring regarding the utilization of Duolingo application through Smartphone. The activity of the service is desperately provide pedagogical commands for all participants how to teach or learn English in an interesting way that is by using Duolingo application. The participants consider that educational Duolingo application is extremely beneficial when to be utilized in English teaching and learning process in classroom.